Experiences with skin and soft tissue infections among people who inject drugs in Philadelphia: A qualitative study. (1st June 2018) - Harris, Robert E.; Richardson, Jessica; Frasso, Rosemary; Anderson, Evan D.
Highlights: PWID understand how to prevent SSTI, but could not apply that knowledge in many environments. PWID delayed healthcare for SSTI because of negative experiences with clinical care. Negative experiences involved inadequate pain care, withdrawal, and stigma. When delaying clinical SSTI care, PWID engaged in high-risk behaviors to manage their symptoms. Self-care included lancing their abscesses and increasing drug use and frequency to manage pain. Abstract: Objectives: To understand how people who inject drugs (PWID) experience skin and soft tissue infections (SSTI) and make decisions to seek or delay medical treatment. Methods: We conducted semi-structured, in-depth interviews in 2015 with 19 PWID at a syringe exchange program in Philadelphia. We analyzed the data using standard qualitative techniques. Results: PWID described adequate knowledge about SSTI, although they could not always implement knowledge about SSTI prevention due to environmental constraints. Participants reported different experiences with incident SSTI. Some sought immediate medical care at initial presentation. Most, however, waited to seek care. Previous positive and negative healthcare experiences, both in general -including stigma and withdrawal- and specific to SSTI, influenced this decision. Among those who delayed medical care, some reported self-treatment, including increased drug use for pain control, and lancing and draining their own wounds. Conclusion: Reducing the incidence of SSTI and promoting earlier treatment are important public health priorities. Both require ongoing attention and improvements to the environments in which PWID inject and receive care.